A indústria na reconfiguraç\~ao territorial brasileira: Novas express\~oes dos dilemas nacionais no Século XXI - Aristides Monteiro Neto; Raphael de Oliveira Silva; Danilo Severian (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– In this article, we discuss the current pattern of territorial reconfi guration of the Brazilian industry, its forms and motivations, in order to put in question some of the most signifi cant challenges of the actual regional issue. We have brought new evidence of how it keeps deconcentrating in the context of the persistent decline in the share of the industry in the national economy. In addition, we focused the analysis on the micro-regional scale which showed the following: i) relevant industrial agglomerations (RIAs) continue to fl ourish in all regions of the country; ii) its preferred place is no longer the polygonal area of Diniz-Crocco (1996); and iii) in terms of industrial job creation, the new RIAs created over the 1995-2015 period generated more jobs than those established before 1995.
Keywords: O14; R11; R12; R58; 330; industry and territory; territorial reconfiguration; industrial dynamism; regional development